Humoral immunity in renal transplantation: epitopes, Cw and DP, and complement‐activating capability – an update. (5th March 2015) - Filippone, Edward J.; Farber, John L.
Abstract Humoral immune responses can destroy a renal allograft. In January 2013, Consensus Guidelines were published regarding testing and management concerns with respect to antibodies in transplantation. New studies have been reported over the past two yr and controversies remain. We review here the new data in light of the Consensus Guidelines and the relevant prior research with emphasis on antibody characteristics and potential for pathogenicity. The heart of immune recognition, epitopes, is stressed, including the realization that DQ (and probably DP) epitopes may be determined not only by eplets within a given α‐ or β‐chain, but also by specific α‐ and β‐chain pairings. The significance of Cw and DP loci are discussed. To better understand which donor‐specific antibodies are pathogenic, IgG subclass determination has been studied, and in in vitro complement fixation assays, such as the C4d and C1q assays, have been evaluated.